Basic Research Approaches to Evaluate Cardiac Arrhythmia in Heart Failure and Beyond - Cumberland, Max J.; Riebel, Leto L.; Roy, Ashwin; O’Shea, Christopher; Holmes, Andrew P.; Denning, Chris; Kirchhof, Paulus; Rodriguez, Blanca; Gehmlich, Katja (Frontiers in Physiology, 2022)
Patients with heart failure often develop cardiac arrhythmias. The mechanisms and interrelations linking heart failure and arrhythmias are not fully understood. Historically, research into arrhythmias has been performed on affected individuals or in vivo (animal) models. The latter however is constrained by interspecies variation, demands to reduce animal experiments, and cost. Recent developments in in vitro induced pluripotent stem cell technology and in silico modelling have expanded the number of models available for the evaluation of heart failure and arrhythmia. An agnostic approach, combining the modalities discussed here, has the potential to improve our understanding for appraising the pathology and interactions between heart failure and arrhythmia and can provide robust and validated outcomes in a variety of research settings. This review discusses the state of the art of models, methodologies and techniques used in the evaluation of heart failure and arrhythmia and will highlight the benefits of using them in combination. Special consideration is paid to assessing the pivotal role calcium handling has in the development of heart failure and arrhythmia.